Led by the carpenter : finding God's purpose for your life! - Kennedy, D. James (Dennis James), 1930-2007. (Nashville, Tenn. : T. Nelson Publishers, 1952)
God's purpose for your life - Made and remade in his image - Living true to our purpose - A pinch of salt - A ray of light - The power of one - God's purpose for your marriage - God's purpose for your children - God's purpose for your church - God's purpose for America - Led by the carpenter.
God's purpose for your life -- Mad and remade in his image -- Living true to our purpose -- A pinch of salt -- A ray of light -- The power of one -- God's purpose for your marriage -- God's purpose for your children -- God's purpose for your church -- God's purpose for America -- Led by the carpenter.
Includes bibliographical references (p. 230-232).
Keywords: Christian life